The Southern Hemisphere Yeast Frontier: From Nature Dwellers to Accomplished Fermenters - Cubillos-Riffo, F (Oxford University Press, 2025)
Yeast biodiversity has been extensively investigated by wealthy countries of the Northern Hemisphere. In contrast, despite the widespread use of fermentation practices in the Southern Hemisphere, yeast diversity in this region remains largely underexplored. However, this trend is beginning to shift as several reports have started to document yeast populations both in the natural environment and in association with the fermentation of various substrates, including grape and apple juice, cocoa and coffee beans, grains, fruits, or tree sap. Numerous yeast species from the Southern Hemisphere have now been described and characterized, with whole-genome sequencing providing essential insights into the evolutionary history of wild yeast isolates from this region. This review highlights the emerging research on yeast biodiversity in the Southern Hemisphere and explores the application of diverse yeast species in the food and beverage industries. © The Author(s) 2025. Published by Oxford University Press on behalf of FEMS.